2013
DOI: 10.1039/c3lc50252j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-coated microfluidic channels for cardiomyocyte culture

Abstract: The research areas of tissue engineering and drug development have displayed increased interest in organ-on-a-chip studies, in which physiologically or pathologically relevant tissues can be engineered to test pharmaceutical candidates. Microfluidic technologies enable the control of the cellular microenvironment for these applications through the topography, size, and elastic properties of the microscale cell culture environment, while delivering nutrients and chemical cues to the cells through continuous med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 46 publications
0
99
0
Order By: Relevance
“…The thickness of the GelMA coating could be adjusted by varying the feeding flow rate, the intensity of the UV light, and/or the concentration of the GelMA prepolymer solution. Moreover, GelMA precursor and cells can be mixed to fabricate microchannels coated with cell-laden GelMA hydrogels [60]. …”
Section: Microfabrication Of Gelma Hydrogelsmentioning
confidence: 99%
“…The thickness of the GelMA coating could be adjusted by varying the feeding flow rate, the intensity of the UV light, and/or the concentration of the GelMA prepolymer solution. Moreover, GelMA precursor and cells can be mixed to fabricate microchannels coated with cell-laden GelMA hydrogels [60]. …”
Section: Microfabrication Of Gelma Hydrogelsmentioning
confidence: 99%
“…4, E and F). Particularly, they found that MeTro coating of microfluidic channels significantly improved adhesion and spontaneous beating of cardiomyocytes compared to surface treatment by gelatin-based materials [150]. …”
Section: Cardiac Bioreactors and Heart-on-a-chipmentioning
confidence: 99%
“…Heart models in microsystems presented in literature allow research on the single cells level (Kaneko et al, 2007, Ges et al, 2008, Murthy et al, 2006, Cheng et al, 2006, multicellular cultures (Nguyen et al, 2009, Nguyen et al, 2015, Pong et al, 2011, Annabi et al, 2013, Ren et al, 2013, Grosberg et al, 2011 and 3D tissue tests (Huang et al, 2007b, Horiguchi et al, 2009, Cheah et al, 2010, Chen et al, 2013 (Table 1). These microsystems are more representative experimental models of the in vivo environment, than conventional culture dishes.…”
Section: Heart Tissue Culture and Toxicity Analysismentioning
confidence: 99%